Job quality of minimum wage workers in Ireland - Redmond, Paul; Ciprikis, Klavs; Elisa, Staffa (ESRI, 2023)
The provision of high-quality jobs is an important component of the policy strategy of organisations such as the ILO, the OECD and the European Union. Job quality can have important implications for employee well-being, as well as being an important component of a well-functioning and productive economy. When considering job quality, the level of pay is often the primary consideration. However, job quality is a multidimensional concept that goes beyond pay, to include factors such as job security, flexibility, union membership, contract type, provision of training, physical risk, and general working conditions. Capturing the multidimensional aspects of job quality is difficult as many surveys do not capture the full range of job quality indicators. In this research, we combine three different datasets to examine the job quality of minimum wage workers in Ireland relative to higher paid workers across a range of dimensions. The datasets we use include the 2022 Irish Labour Force Survey, the 2015 European Working Conditions Survey, and the 2014 European Skills and Jobs Survey. As we are focused on minimum wage employment, which by definition are low-paying jobs, we focus on aspects of job quality beyond remuneration. We find that minimum wage employees are approximately 10 percentage points more likely than higher paid employees to fear job loss and to hold temporary employment contracts, and approximately 5 percentage points more likely than higher paid employees to want to work more hours than they currently do. Our results also show that minimum wage employees are approximately 20 percentage points less likely to be members of a trade union. Minimum wage employees also appear to have less flexibility in their jobs, as we find that they are 20 percentage points less likely to be able to work from home. Compared to higher paid workers, minimum wage employees are also found to work longer shifts (more than ten hours) that coincide with more unsocial times (Saturdays and Sundays). They are also 13 percentage points more likely to work in jobs in which their skills are underutilised. This is reflected in the fact that minimum wage employees also report lower job complexity and lower levels of computer usage compared to higher paid employees, and are less likely to receive training in their jobs. However, while most job quality indicators show that minimum wage jobs tend to be lower quality, there are three exceptions. Minimum wage employees are more likely to be in jobs where they have a choice in the colleagues they work Executive summary | vii with and in the hours that they work. In addition, minimum wage employees are more likely to be in jobs where the boss is successful in getting people to work together. In addition to facing low levels of pay, our research indicates that, overall, minimum wage workers may also face less favourable job quality conditions as measured by a variety of factors. This highlights the importance of providing not only a minimum level of pay, but also ensuring a minimum level of acceptable terms and conditions of employment. For many low-paid workers, minimum wage employment may be a relatively short-term stepping-stone to higher pay. However, for others it may be a longer-term arrangement. The combination of low pay and other potentially unfavourable job quality measures is of particular concern for individuals that may be long-term minimum wage employees.